Moving in a hierarchized landscape; Changing border regimes in Central Kalimantan - Lumenta, Dave (Wacana, Journal of the Humanities of Indonesia, 2011)
Transnational mobility is a common feature among borderland communities. Central Borneo has been a relatively fluid and open riverine-based socio-cultural and economic space since the arrival of colonial states, without much interference from the establishment of international boundaries on local cross-border mobility practices. This applies to the Kenyah, a cluster of related ethnic groups occupying the Apokayan plateau in East Kalimantan (Indonesia), who are historically an integral part of the socio-cultural and economic fabric throughout the major riverine systems of Sarawak (Malaysia). Despite the relative absence of states, Central Borneo has not escaped the onslaught of social differentiation embedded in nation-state identities. The penetration of Sarawak's logging industry has brought the terrestrial re-ordering of the Bornean landscape away from the relative egalitarian social order of river basins into hierarchical social relations embedded in capitalistic modes of production. This has brought about the construction of the Kenyah's visibility as an "Indonesian underclass" inside Sarawak.